The long Earth - Pratchett, Terry (HarperCollins, 2012)
1916: The Western Front. Private Percy Blakeney wakes up. He is lying on fresh spring grass. He can hear birdsong and the wind in the leaves. Where have the mud, blood, and blasted landscape of no-man's-land gone? For that matter, where has Percy gone? 2015: Madison, Wisconsin. Police officer Monica Jansson is exploring the burned-out home of a reclusive--some say mad, others allege dangerous--scientist who seems to have vanished. Sifting through the wreckage, Jansson find a curious gadget: a box containing some rudimentary wiring, a three-way switch, and a potato. It is the prototype of an invention that will change the way humankind views the world forever. The "stepper" enables a person using it to step sideways into another America, another wherever that person happened to be, another Earth. And if the person using it keeps on stepping, they keep on entering even more Earths. This is the Long Earth. And the further away a stepper travels, the stranger -- and sometimes more dangerous -- the Earths become.